Respuesta :

Answer: y = 3x + 2

Step-by-step explanation:

[tex]\dfrac{x-x_{1} }{x_{2} -x_{1} } =\dfrac{y-y_{1} }{y_{2} -y_{1} }\\[/tex]

Let's choose two arbitrary points on the graph.

For example, let these be points with coordinates (1, 5) and (2, 8).

Substitute the coordinates of these points into the above formula and derive the equation of a straight line.

[tex]\dfrac{x-1}{2-1} =\dfrac{y-5}{8-5}\\\\\dfrac{x-1}{1} =\dfrac{y-5}{3}\\\\3(x-1)=y-5\\3x-3=y-5\\y=3x-3+5\\y=3x+2[/tex]

hope this helps! feel free to clarify
Ver imagen niclahhh